Geography of Emigration and Cultural Interaction: Russian-Language Drama in the European Cultural Landscape - Kurant, Elena (Literatūra, 2025)
In 2022, Russian-language drama faced a new wave of emigration caused by political repression, censorship, and a principled anti-war stance of many representatives of the creative intelligentsia.Russian-language plays are becoming part of the European theatrical landscape, entering into dialogue with local traditions, and receiving support from independent theatres, festivals, and new institutional initiatives. The subject of analysis in this article is the phenomena that testify to the profound processes of transculturation as a manifestation of contemporary cultural perception. This study focuses on the artistic strategies of expression under conditions of forced displacement, as well as on the ways in which contemporary playwrights’ texts are being integrated into the European theatrical and cultural context. Emigrant drama becomes a kind of platform for demonstrating postnational thinking, which is expressed in the aspiration to create an artistic statement at the intersection of the personal and the political, the local and the global. This is exemplified by the theatrical experiments of N. Lizorkina, M. Davydova, M. Ilinchik, and P. Borodina.
Keywords: contemporary drama; theatre in exile; transculture; Echo of Lyubimovka; anti-war play